2016
DOI: 10.1016/j.apsusc.2015.11.203
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent surface porosity of Nb2O5 under high-flux, low-energy He+ ion irradiation

Abstract: The present study reports on high-flux, low-energy He + ion irradiation as a novel method of enhancing the surface porosity and surface area of naturally oxidized niobium (Nb). Our study shows that ion-irradiation-induced Nb surface micro-and nano-structures are highly tunable by varying the target temperature during ion bombardment. Mirrorpolished Nb samples were irradiated with 100 eV He + ions at a flux of 1.2×10 21 ions m-2 s-1 to a total fluence of 4.3×10 24 ions m-2 with simultaneous sample annealing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 41 publications
3
19
1
Order By: Relevance
“…Also, the difference in the ion flux by~20 % (2:4 À 3:1 Â 10 22 m À2 ) had a minor effect, considering the fact the irradiationtime was changed by a factor of three or greater. As was discussed previously, [48] the surface was easily oxidized naturally at room temperature. We also observed the cross section of FN layers both on 3 h and 10 h irradiated Nb samples; the thickness of the FN layer was almost the same on both samples.…”
Section: Morphology Changesmentioning
confidence: 75%
“…Also, the difference in the ion flux by~20 % (2:4 À 3:1 Â 10 22 m À2 ) had a minor effect, considering the fact the irradiationtime was changed by a factor of three or greater. As was discussed previously, [48] the surface was easily oxidized naturally at room temperature. We also observed the cross section of FN layers both on 3 h and 10 h irradiated Nb samples; the thickness of the FN layer was almost the same on both samples.…”
Section: Morphology Changesmentioning
confidence: 75%
“…Ex situ XPS has previously been reported by us1920 to be a valuable technique not only for determining surface chemistry and oxidation states of samples, but also for indirectly measuring surface roughness post-irradiation. Since a roughened surface has a larger effective surface area, and larger surface area provides increased number of sites available for oxidation, one would expect a very rough surface to oxidize more efficiently when exposed to air.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are only a few preliminary studies investigating the response of these alternative refractory metals to high fluxes of He and H isotopes. It has been shown that under these similar He + ion irradiation conditions, significant nanostructuring is also observed in most other refractory metals such as molybdenum (Mo)1819, niobium (Nb)20, and vanadium (V)21. However, similar preliminary temperature-dependent studies in Ta22 show that Ta does not form the same high aspect ratio surface structures as observed in W, Mo, Nb, and V; rather, Ta only forms shallow surface pores when irradiated with high-flux, low-energy He + ion irradiation.…”
mentioning
confidence: 99%
“…All irradiations were performed in ultra-high vacuum (UHV) chamber with a base pressure of 5.0  10 -8 Torr; however, the working pressure during ion irradiation was 1.0  10 -4 Torr. The selected ion energy (100 eV), ion-flux (7.2  10 20 ions m -2 s -1 ), ion-fluence (2.6  10 24 ions m -2 ), and range of target temperature (823-1173 K) were based on our previous studies involving He + -induced surface modifications in refractory metals [40,41,43,44]. For precise temperature measurement, we used thermocouples rather than radiation thermometers; a thermal-feedback mechanism in the sample heater were corrected for the ion- Ocean Optics was used for signal detection.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…This study is also significant in the understanding of microstructure evolution and fuzz formation on high-Z refractory metals for fusion applications. As with W [8,9,[36][37][38][39], Mo [40][41][42], Ta [43], and Nb [44], the He + ion-irradiated V surface could also have a weakness against plasma and/or ion heat flux. Therefore, such V nano-and submicron-structures may not be favorable for protecting the V surface from possible melting and erosion.…”
Section: Introductionmentioning
confidence: 99%